Pengaruh Motivasi Belajar dan Fasilitas Laboratorium Terhadap Prestasi Belajar Mahasiswa Jurusan Akuntansi Syariah FEBI UIN K. H. Abdurrahman Wahid Pekalongan - Nuzulul (Integrated Lab Journal, 2022)
One of the factors that determine student success in achieving an achievement on campus is motivation, which plays an important role. A student's motivation in learning always experiences changes that can be reduced. Reduced enthusiasm/passion or even absent in learning then automatically reduced enthusiasm in these activities. Existing facilities in the laboratory have contributed to success in practicum activities because they have an influence on student achievement in learning. The purpose of this research was to analyze how the influence of learning motivation (X1), laboratory facilities (X2) and learning achievement (Y). This research is in the type of quantitative research by distributing questionnaires to fifth semester students of the Department of Sharia Accounting FEBI UIN K.H. Abdurrahman Wahid Pekalongan, totaling 111. The data that has been processed in this study uses a descriptive analysis and multiple linear regression tests and uses the IBM SPSS 22 tool. The results show that learning motivation significantly influences learning achievement t count with learning motivation variable, namely 6,881 > t table of 1.98472 and a significance value of 0.000 <0.05. Laboratory facilities significantly affect learning achievement where t count is 5.396 > t table is 1.98472 and a significant value is 0.00 <0.05. After the Anova test was carried out, learning motivation and laboratory facilities together had an influence on learning achievement where the regression significance value of 0.00 was less than alpha 0.05 indicating that Ha3 was accepted and H03 was rejected. Then the Fcount value obtained by a number of 60.615 is greater than the Ftable of 3.09.